Who gets the schools? Political targeting of economic and social infrastructure provision in Zambia - Stefan Leiderer (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
This paper contributes to a growing body of literature on the political economy of public finance in developing countries. Its main methodological interest is to demonstrate the usability of household-level data to study political economy features of public finances in developing countries that commonly escape empirical scrutiny due to poor data availability. The empirical interest is in testing whether there is evidence for or against either of two competing models of political targeting of public sector spending: the swing-voter versus the core-voter model, the proposition being that in “typical” neo-patrimonial regimes in sub-Saharan Africa, the corevoter model should prevail. I use data from Zambia's Living Conditions Monitoring Survey (LCMS) to investigate whether there is evidence that the ruling party in Zambia followed political motives in targeting public infrastructure spending at the turn of the millennium, and whether there is evidence that such targeting falls in line with either of these two models. I find strong and robust evidence for the core-voter model applying to social infrastructure provision in Zambia. The findings suggest that it is primarily the construction of new health and education facilities that is affected by political targeting, whereas there is no strong evidence for such targeting for the improvement and rehabilitation of existing infrastructure. For roads construction or rehabilitation, I find no evidence of similar political targeting.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Demokratie und Autokratie; Governance